Peran UPZ dalam meningkatkan pengumpulan ZIS BAZNAS kota tebing tinggi - Vina Cynthiasari; Zuhrinal M. Nawawi (Jurnal Riset Pendidikan Ekonomi, 2022)
One function of the BAZNAS Tebing Tinggi is collect zakat, infak, and shadaqah, but the limitations it has encouraged the BAZNAS Tebing Tinggi to maximize the role and duties of UPZ. The research is aimed at figuring out UPZ’s role in boosting ZIS collections of BAZNAS Tebing Tinggi. The research site is BAZNAS Tebing Tinggi office, which ran from 17 January 2022 to 17 February 2022. The study employed a descriptive qualitative method by using two data sources that were generated from interviews with staff BAZNAS Kota Tebing Tinggi or called primary data and data obtained from boooks, journals, thesis, and notes or called secondary data. Research shows that the amount of money that goes into the BAZNAS Kota Tebing Tinggi via UPZ is down through the year, but the ZIS collected by UPZ to BAZNAS Kota Tebing Tinggi is highest in value compared to the collection from other sources. The more funding that can be collected, the more channeling that can be given to those who are entitled to it.